Case stories in general practice: a focus group study. Issue 4 (8th August 2012) - Abildsnes, Eirik; Flottorp, Signe; Stensland, Per
Abstract : Objectives: To explore the interactive process of sharing case stories in small-group activity in general practice. Design: Qualitative focus group study. Setting: Peer-group meetings of doctors attending specialist training or continuous medical education in general practice. Participants: Twenty female and 30 male doctors working in general practice in Norway. Results: The storyline of case presentations included detailed stories with emotional engagement, co-authored by other group members. The stories initiated discussions and reflections concerning patients' and doctors' perspectives, medical ethics as well as clinical problems. The safe atmosphere allowed testing out boundaries of socially shared knowledge. Conclusions: Sharing case stories in small groups in general practice initiated interaction that facilitated meaning-making, reflection and peer support.